2019
DOI: 10.1177/0047287519846430
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emigration on Tourism Outward Foreign Direct Investment: Evidence from China

Abstract: With the growth of economic globalization and international tourism, tourism outward foreign direct investment (OFDI) has become a significant phenomenon in the development of the tourism industry. This article aims to estimate how emigration affects OFDI in tourism. It develops the theoretical framework of the effects of emigration on tourism OFDI, including the outbound tourism effect, the economic effect, the cultural effect, and the social effect. The empirical evidence in China reveals a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Some researchers have highlighted the importance of flexible urban transportation systems to help curb growing tourist demand (Gössling, 2017;Riganti & Nijkamp, 2008). Thus, efficient and diverse transportation systems have been suggested to have the ability to improve tourists' satisfaction and their image of the destinations visited (Chen et al, 2019;Song, Shi, Chen, Nijkamp, et al, 2020). The tourism sector also offers an interesting example of flexible ride-sharing, since transportation congestion (particularly waiting in a queue to use vehicles) is often caused by excess demand and seasonality (Riganti & Nijkamp, 2008).…”
Section: Ride-sharingmentioning
confidence: 99%
“…Some researchers have highlighted the importance of flexible urban transportation systems to help curb growing tourist demand (Gössling, 2017;Riganti & Nijkamp, 2008). Thus, efficient and diverse transportation systems have been suggested to have the ability to improve tourists' satisfaction and their image of the destinations visited (Chen et al, 2019;Song, Shi, Chen, Nijkamp, et al, 2020). The tourism sector also offers an interesting example of flexible ride-sharing, since transportation congestion (particularly waiting in a queue to use vehicles) is often caused by excess demand and seasonality (Riganti & Nijkamp, 2008).…”
Section: Ride-sharingmentioning
confidence: 99%
“…As a result, past studies found a positive relationship between the size of the Chinese community in a host country and China's OFDI (Blomkvist, & Drogendijk, 2016;Karreman et al, 2017). This effect was also reported when analyzing Chinese tourism OFDI (Song et al, 2020). Hence, the percent of Chinese migrants over total population in each host country was included as a control variable, using figures from the United Nations Population Division (Quer et al, 2019;Song et al, 2020).…”
Section: Control Variablesmentioning
confidence: 81%
“…Past research found that a higher number of tourists from a home country in a tourist destination led to a higher number of OFDIs by firms from that home country in that destination (Santos et al, 2016). Prior studies on Chinese tourism reached similar results (Li, Huang, & Song, 2017;Song, Shi, Chen, Nijkamp, & Li, 2020). Accordingly, the number of Chinese tourist arrivals to each host country was considered as a control variable, with one-year lag and a log transformation (Deng et al, 2019).…”
Section: Control Variablesmentioning
confidence: 99%
“…International migration and tourism arrivals are perhaps the two most important social phenomena involving the movement of people in this new era of globalization (UNWTO 2009). The link between them has been highlighted in several economic and tourism studies (Buckley et al 2020; Song et al 2020; Dwyer et al 2014; Feng and Page 2010). Two main concepts can be identified in the migration-tourism nexus, Tourism-led Migration (TLM) and Migration-led Tourism (MLT), which can be understood as a circular relationship (UNWTO 2009).…”
Section: Literature Review: the Nexus Among Migration Remittances And Tourismmentioning
confidence: 95%